A new class of polynomials and the polynomials related to them - Chandel, R. S.; Singh Chandel, R. C. (Rev. Téc. Fac. Ing. Univ. Zulia)
The present paper deals with the study of a general class of polynomials. We mention some particular cases deduce some of their properties.